Determining the Best Zone for Waste Storage Ponds: Integrating DEM analysis and Satellite Gravity data in the Prospect Area of Ungaran Geothermal Mining Working Area, Semarang, Indonesia. - Humairoh, Wahyuni Annisa -; Mardiati, Dani; Ambara Putra, I Putu Raditya (Journal of Applied Sciences, Management and Engineering Technology, 2025)
The Ungaran Geothermal Mining Working Area, Mount Ungaran, has geothermal prospects around the Gedongsongo and Nglimut areas, which have the potential to develop as Indonesian geothermal exploration projects. The challenges in developing geothermal exploration projects in Indonesia are the PLTP sector, which generates geothermal waste in the form of brine and geothermal mud. If discharged into the environment, this waste can pose a threat to human health and ecosystems. This study aimed to specify the most suitable zone for waste storage ponds in the Ungaran geothermal prospect area. The method integrates data analysis of Digital Elevation Model (DEM) imagery, Landsat imagery, and air gravity data, which produces integrated maps, such as Maps of Fault and Fractures density and Maps of Land Cover. Second vertical derivative (SVD) analysis from air gravity data is also used to ensure the presence of a structure. There are five parameters for determining the pond-making zone: Not a residential area with a slope of less than 15%, distance from the fault is more than 200 m, distance from the road is more than 100 m, and distance from areas of geothermal manifestations such as hot springs and fumaroles is more than 200 m. Based on the interpretation of the integrated maps resulting from the analysis, several zones are suitable for creating waste storage ponds in the Nglimut and Gedongsongo prospect areas. The Nglimut area has potential zones, in contrast. In the Gedongsongo area, there are no potential zones. The Nglimut prospect has two possible zones; the best zone is N2, where all five parameters are perfectly satisfied. The northern area of N1 has one geothermal manifestation (hot spring). The best-to-fair zones are N2 and N1.